Effects of plant growth promoting Rhizobacteria microbial on the growth, rhizosphere soil properties, and bacterial community of Pinus sylvestris var. mongolica seedlings. Issue 4 (19th May 2021) - Song, Qian; Song, Xiaoshuang; Deng, Xun; Luo, Jiayu; Wang, Junkai; Min, Kai; Song, Ruiqing
ABSTRACT: The use of plant growth promoting rhizobacteria (PGPR) instead of pesticides to promote plant growth has received widespread attention. In this study, potted experiments and high-throughput Illumina MiSeq sequencing technology were used to evaluate the effects of inoculation of three PGPR strains on the biomass of Pinus sylvestris var. mongolica and soil bacterial diversity. The results showed that the three PGPR strains all have the ability to secrete indole-3-acetic acid (IAA), dissolve inorganic phosphorus and produce siderophores. After inoculation with the PGPR strain, the plant seedling height increased significantly by 27.60%, and the root length increased significantly by 47.88% ( P  < 0.05), soil available nitrogen, phosphorus and potassium increased by 19.05%-47.62%, 26.63%-83.32% and 87.70%-98.10% respectively ( P  < 0.05). High-throughput sequencing results showed that the abundant bacterial phyla in soil include: Acidobacteria, Patescibacteria, Bacteroidetes, Chloroflexi, Gemmatimonadetes, Firmicutes, Actinobacteria, and Proteobacteria. The Monte-Carlo permutation test indicated that soil AP, TP, AK, and OM were the main environmental parameters influencing the composition of the microbial communities (at the genus level). This study provides basic data references for PGPR strains to improve the soil microecological environment and promote the growth and development of Pinus sylvestris var. mongolica seedlings.